Realizing the genetic potential of black-and-white cows of different genotypes by the kappa-casein gene - A. D. Lemyakin; L. S. Badanina; K. D. Sabetova; A. A. Chaitskiy; P. O. Schiogolev (Аграрная наука Евро-Северо-Востока)
Milk quality indicators are one of the main components of the breeding value of dairy cattle. The experience of many countries demonstrates that the Holsteinization of local cattle breeds is accompanied by an increase in the volume of milk produced while reducing its quality characteristics in particular to its cheese suitability. Solving this problem only by means of traditional breeding is difficult but it is possible to facilitate this task with application of modern molecular genetic methods and marker-oriented selection. The objective of the research was to assess the genetic potential of dairy performance of cattle with different genotypes by the kappa-casein gene (CSN3). The study was conducted on 104 purebred Russian black-and- white cows selected from the herds of the Yakovlevskoye APC and Raslovskoye APC. It was determined that the desired CSN3BB genotype was most common in 61 % of animals. As part of the study, the comparison of the experimental animals' own milk productivity with the productivity of their ancestors was carried out which made it possible to assess their genetic potential. The analysis showed that in the Yakovlevskoye APC, the protein content in milk in carriers of the CSN3AA genotype was significantly less than in carriers of the CSN3AB (P < 0.05) and CSNBB (P < 0.001) genotypes. There were no statistically significant differences in other productivity indicators, although the carriers of the CSNAB genotype (100.9%) differed in the greatest realization of the genetic potential in terms of the mass fraction of fat in milk, and cows with the CSNBB genotype (106.7 and 103.9 % respectively) in milk yield and protein content in milk. In the Raslovskoye APC, the greatest realization of the genetic potential in milk yield (119.5 %) was distinguished by carriers of the CSNAA genotype and the greater potential of fat and protein in milk were shown by animals with the CSNBB genotype (112.3 % and 103.7 %, respectively). Thus, the polymorphism of bovine kappa-casein gene has a significant impact both on the protein content in milk and on the realization of the genetic potential for this indicator of productivity. The obtained research results are important for breeding work with Russian black-and-white cattle aimed at improving the cheese suitability of milk.